Remote Control Powerboat II (Remote Control System) - Diana, Spencer (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Remote control system is a simple wireless technology, yet capable of delivering modern convenience to human in this contemporary age. The core of this technology is just a transmitter to transmit information signals and a receiver to decode the instructions. Remote control system offers a solution to the problem of controlling devices from afar as it uses free space as its transmission medium. Thus, the distance between corresponding transmitter and receiver are not limited by the maximum length of wire, waveguide etc. The application of a remote control system is endless. This technology can be incorporated to a variety of equipments such as spy airplane, universal remote control, garage door opener, robotic equipments, toys and many more. This project concentrates on integrating the remote control system with scaled size powerboat complete with its own mechanical system. The remote control system consists of a simple transmitter and receiver. The transmitter and the receiver will be able to transmit and receive control information entered by the user. Meanwhile, the scaled size powerboat is made from fiber and/or plywood. The movement of the powerboat is control by the receiver according to the control information. This movement is generated by the mechanical system of the powerboat. The mechanical system of the remote control powerboat is made from a modified two-stroke bush cutter engine and other miscellaneous items such as servo motor and propeller